RE-EVALUASI PENERAPAN SISTEM PENGUMPULAN TOL ELEKTRONIS DI INDONESIA - Rikki Sofyan Rizal; Rudy Hermawan K; Titi Liliani S (Universitas Widyatama, 2019)
In 2007, for the first time, an electronic toll collection system was implemented to overcome queues in toll gate, however its application was only limited for several toll road segments in Indonesia. After that in 2017 the Minister of Public Works and Public Housing issued regulation Number 16 / PRT / M / 2017 concerning Cashless Transactions on Toll Road, in October 31th 2017, to implement an electronic toll collection system in every toll gates in Indonesia. For this reason, it is necessary to evaluate the application of electronic transaction, systems that have been implemented at this time. From the analysis, it is obtained with this electronic system the average period of transaction for GTO is 3 seconds and GSO is 3.6 seconds, so that it meets the Toll Road SPM which is less than 5 seconds. For the results of capacity calculation, free flow booth has the highest capacity compared to the GTO and GSO. As well as for queuing analysis with booth capacity greater than the arrival rate of vehicles in all types of booth transaction, there is no queue at the booth transaction. On the other hand, with the implementation of the electronic toll collection system, currently 86% of respondents feel satisfied and there are several benefits obtained by toll operators such as the lower operating costs of booth. In the future BUJT has made preparations for the implementation of free flow transactions by coordinating between toll operators regarding the technology systems and processes to be implemented.